Basic principles of anchorage: a review - Sharma, Disha; Thakur, Gaurav; Gurung, Deepak; Thakur, Amrita (International Journal of Research in Medical Sciences, 2024)
During orthodontic treatment, teeth are subjected to various forces and moments, which generate reciprocal forces of equal magnitude but opposite direction. To prevent unwanted tooth movements and ensure successful treatment outcomes, it is essential to effectively manage these reciprocal forces. Numerous studies have explored different anchorage systems in terms of their application, function, and effectiveness. However, practitioners often find it challenging to interpret these findings due to the diversity in study designs, sample sizes, and methodologies. A solid understanding of anchorage principles is crucial for applying them effectively. Anchorage control is a critical factor in designing orthodontic appliances. While extraoral devices can provide stable anchorage, their effectiveness heavily relies on patient cooperation. In contrast, intraoral anchorage tends to be less stable, often necessitating complex appliances and sometimes the extraction of teeth. Nonetheless, intraoral systems have the advantage of requiring less patient compliance. To achieve treatment objectives, it is vital to establish a biomechanical setup that delivers the appropriate type and magnitude of force. This foundational understanding of anchorage principles will enhance the effectiveness of orthodontic treatments.